1998
DOI: 10.1175/1520-0477(1998)079<1307:hocw>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Highlights of Coastal Waves 1996

Abstract: Some of the highlights of an experiment designed to study coastal atmospheric phenomena along the California coast (Coastal Waves 1996 experiment) are described. This study was designed to address several problems, including the cross-shore variability and turbulent structure of the marine boundary layer, the influence of the coast on the development of the marine layer and clouds, the ageostrophy of the flow, the dynamics of trapped events, the parameterization of surface fluxes, and the supercriticality of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 35 publications
4
60
0
Order By: Relevance
“…The close correlation between the spatial distribution of the surface stress in the region of the expansion fan and that of the coldest sea-surface temperatures has been noted in a number of papers (Rogers et al, 1998;Dorman et al, 1999;Tjernström and Grisogono, 2000;Brooks, 2001) -cold upwelling is observed along the whole West Coast, driven by Ekman pumping, but is enhanced in the lee of a headland by the strong horizontally divergent flow in the expansion fan. The colder SST results in increased stability within the lower BL but appears to have little impact on the dynamics of the flow Tjernström, 1999).…”
Section: Synoptic Situation and Mesoscale Dynamicsmentioning
confidence: 60%
See 3 more Smart Citations
“…The close correlation between the spatial distribution of the surface stress in the region of the expansion fan and that of the coldest sea-surface temperatures has been noted in a number of papers (Rogers et al, 1998;Dorman et al, 1999;Tjernström and Grisogono, 2000;Brooks, 2001) -cold upwelling is observed along the whole West Coast, driven by Ekman pumping, but is enhanced in the lee of a headland by the strong horizontally divergent flow in the expansion fan. The colder SST results in increased stability within the lower BL but appears to have little impact on the dynamics of the flow Tjernström, 1999).…”
Section: Synoptic Situation and Mesoscale Dynamicsmentioning
confidence: 60%
“…The NCAR C-130 Hercules has an extensive suite of instrumentation for the measurement of meteorological, turbulent, radiative, and microphysical variables; details can be found in Rogers et al (1998). All data are sampled at 25 Hz; turbulence quantities are calculated using this high-rate data, while mean quantities are derived from one second averages.…”
Section: Aircraft Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rogers et al, 1998;Rahn and Garreaud, 2010) as well as modelling and theoretical studies (e.g. Burk and Thompson, 1996;Mun˜oz and Garreaud, 2005).…”
Section: Introductionmentioning
confidence: 99%